Light‐Driven Catalyst‐Free Access to Phthalazines: Entry to Antiviral Model Drugs by Merging Domino Reactions. Issue 5 (7th November 2022) - Guryev, Anton; Schuster, Florian; Herrmann, Lars; Hahn, Friedrich; Wangen, Christina; Hodek, Jan; Weber, Jan; Marschall, Manfred; Tsogoeva, Svetlana B.
Abstract: We report the development of a metal‐free four‐step one‐pot synthetic strategy to access high‐value functionalized phthalazines using o‐methyl benzophenones as starting compounds. Combining a light‐mediated enolization of o‐methyl benzophenones/Diels‐Alder reaction domino process with a subsequent deprotection/aromatization domino reaction in one‐pot leads to sustainable and efficient organic synthesis. The tangible advantages, i. e., absence of catalysts or additives, utilization of commercially available and/or easily accessible substrates, mild reaction conditions, simplicity, and single work‐up procedure, make this combined process highly appealing for the direct construction of various 1‐aryl‐phthalazines. Importantly, in vitro bioactivity evaluation of these newly prepared heterocyclic compounds demonstrated a strong antiviral efficacy against major human pathogens like HCMV and SARS‐CoV‐2. Abstract : Light as air: A straightforward metal‐free four‐step one‐pot synthetic strategy to access new high‐value functionalized phthalazines was developed. Combining a facile light‐mediated enolization of o‐methyl benzophenones/Diels‐Alder reaction domino process with a subsequent deprotection/aromatization domino reaction leads to waste‐reducing and cost‐effective synthesis of new antiviral model drugs.